2005
DOI: 10.1177/1096348004267518
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Experience, Subjective Knowledge, and Objective Knowledge on Sources of Information used in Consumer Wine Purchasing

Abstract: The decision to consume wine has been associated with variables such as product involvement, variety seeking, demographic characteristics, experience, and sources of information. The purpose of this study was to examine the decision process for wine selection in different situations. Data were collected from a sample of wine consumers in Texas and a total of 632 completed responses were obtained. The questionnaire was designed to determine consumer experience, knowledge, and use of differential sources of info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
289
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(307 citation statements)
references
References 27 publications
12
289
0
6
Order By: Relevance
“…Thus, it refers to what an individual actually knows about a type of product/issue/object [30]. On the other hand, subjective knowledge refers to the individual's perceptions or assessments of what and how much they know about a product/issue/object [47,48].…”
Section: Environmental Knowledge and Classificationsmentioning
confidence: 99%
“…Thus, it refers to what an individual actually knows about a type of product/issue/object [30]. On the other hand, subjective knowledge refers to the individual's perceptions or assessments of what and how much they know about a product/issue/object [47,48].…”
Section: Environmental Knowledge and Classificationsmentioning
confidence: 99%
“…This information source was regarded as critical by these respondents (with a mean score of 4.17 out of a possible 5) as they believed that this internal information which derived from their past experience and knowledge could impact either positively or negatively on their choice of travel agency to patronise in the future. Furthermore it was argued that where things are more convenient, they are more likely to be used (Dodd et al, 2005) and in this study, the convenience of accessing this information source together with its highly reliable first-hand experience would have contributed to its importance.…”
Section: Resultsmentioning
confidence: 82%
“…Information sources that consumers might use to assist in their selecting of travel agencies could vary and might differ in accordance to decision making situations. Studies have investigated models of information search behaviour and information source usage in different situations (for example Bieger & Laesser, 2004;Dodd, Laverie, Wilcox & Duhan, 2005;Fodness & Murray, 1999;Vogt & Fesenmaier, 1998). Whilst there is no single unique classification system for information sources, they can generally be classified as: (a) internal and external sources, (b) personal and impersonal sources, (c) informal and formal sources, and (d) commercial and non-commercial sources (for example Crotts, 1999;Dodd et al, 2005;Fodness & Murray, 1997;Raitz & Dakhil, 1989).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately for wine merchandisers, front and back label information, as well as shelf talkers and displays, did not score highly in terms of decision-making on selecting wine in retail settings (Thatch, 2008). However, Dodd, Laverie, Wilcox, and Duhan's (2005) results indicated that wine guides, reviews, and advertising were used to make purchase decisions.…”
Section: Consumer Behavior and Winementioning
confidence: 99%